2021
DOI: 10.1016/j.zefq.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Klinik-Weiterempfehlung bei Reha-Erfolg: Erfahrungsberichte von Rehabilitanden auf einer Klinik-Bewertungsplattform

Abstract: Hintergrund: Feedback von Patienten über erlebte Versorgungsaspekte erfolgt auch in der Rehabilitation inzwischen zunehmend online, beispielsweise auf Bewertungsportalen. Daher soll untersucht werden, welche von Rehabilitanden auf der für Reha-Kliniken führenden Bewertungsplattform Klinikbewertungen.de veröffentlichten Versorgungsaspekte mit der Weiterempfehlung einer Rehaklinik und welche negativen Aspekte mit der Nicht-Weiterempfehlung assoziiert sind. Methode: Eingeschlossen wurden Reha-Kliniken der Rentenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although British and Canadian reviewers tend to complain about staff prerequisites, Germans are more likely to criticize the care environment and patient-centered processes [ 25 ]. Considering the context of inpatient rehabilitation clinics, Sander et al [ 26 ] conducted an initial examination of web-based patient reports to investigate determinants associated with recommending inpatient rehabilitation clinics, and identified perceived therapy successes as well as process of care parameters to be associated with clinic recommendations. Although aspects of patient-centered processes and expected outcomes were quantitatively subordinate, the qualitative in-depth analysis of the present study indicates a relationship between positively reported expected outcomes and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although British and Canadian reviewers tend to complain about staff prerequisites, Germans are more likely to criticize the care environment and patient-centered processes [ 25 ]. Considering the context of inpatient rehabilitation clinics, Sander et al [ 26 ] conducted an initial examination of web-based patient reports to investigate determinants associated with recommending inpatient rehabilitation clinics, and identified perceived therapy successes as well as process of care parameters to be associated with clinic recommendations. Although aspects of patient-centered processes and expected outcomes were quantitatively subordinate, the qualitative in-depth analysis of the present study indicates a relationship between positively reported expected outcomes and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%